Developing of Key Competencies by Means of Augmented Reality at CLIL Lessons - Мерзликін, Олександр; Тополова, Ірина; Тронь, Віталій (Pedagogy of Higher and Secondary Education, 2018)
Merzlykin O.V., Topolova I. Yu. and V.V. Tron Developing of Key Competencies by Means of Augmented Reality at CLIL Lessons. Using of new learning and IC technologies is necessary for effective learning of modern students. Their specific educational needs are: using of mobile ICTs, collaboration, challenging tasks and entertainment. Appropriate learning environment should be created to satisfy all these demands. It ought to deal with cloud-based technologies (for 24/7 access, individual and group work according to a personal schedule), augmented reality (for creating of firm links between real and virtual objects), content and language integrated learning (for immersion in an additional language and creation challenging groups and personal tasks in language and non-language subjects). Using these technologies in complex provides social and ICT mobility and creates positive conditions for developing 9 of 10 key competencies. The paper deals with the features, problems and benefits of technologies’ implementation in secondary schools. To sum up, in spite of all difficulties, this environment helps students to get some practical experience in using foreign languages and understanding abstract nature concepts; to develop language and research competencies and to remain motivated (and self-motivated) in learning Science and English.